2018
DOI: 10.1080/10803548.2018.1452457
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial risks in small enterprises: the mediating role of perceived working conditions in the relationship between enterprise size and workers’ anxious or depressive episodes

Abstract: This study highlights perceived working conditions as an explanation of the effects of enterprise size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 36 publications
0
14
0
4
Order By: Relevance
“…Compared with medium and large sized firms, most small sized business have a weak financial structure and are more likely to fight for survival . Their owners have a broad range of responsibilities, greater stake in their business, and tend to work long hours, consequently placing their health and safety issues at a low priority . Moreover, small businesses’ entry and exit is easy and small business owners in Korea tend to advance into self‐employment without sufficient preparation .…”
Section: Introductionmentioning
confidence: 99%
“…Compared with medium and large sized firms, most small sized business have a weak financial structure and are more likely to fight for survival . Their owners have a broad range of responsibilities, greater stake in their business, and tend to work long hours, consequently placing their health and safety issues at a low priority . Moreover, small businesses’ entry and exit is easy and small business owners in Korea tend to advance into self‐employment without sufficient preparation .…”
Section: Introductionmentioning
confidence: 99%
“…Five studies included only SME-managers and enterprise owners [ 57 , 58 , 59 , 60 , 61 ]. Some studies used data from nationwide surveys that provided a large sample size and included a range of economic sectors and branches [ 29 , 30 , 62 , 63 , 64 , 65 , 66 , 67 ]. Other studies included only participants of a single enterprise [ 68 , 69 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, we identified four studies investigating the differences of job stress in SMEs compared to large firms [ 30 , 31 , 63 , 67 ]. Whereas Tsai et al [ 31 ] found higher levels of job stress and “higher favorable attitudes toward managers” in SMEs, Lai et al [ 63 ] obtained no firm size effect on overall job stress after adjusting for covariates including individual and organizational characteristics (information on job tenure, contractual status, gender, age, marital status, number of children, caring responsibility, long-term illness, academic qualification, weekly pay, work condition changes, organizational support) in an European (U.K.) sample.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations